How Does Knowledge Management Affect Employee Performance? : Systematic Literature Review - Riki Nuryadin; Disman, Disman; Santoso, Budi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to explore and analyze the relationship between knowledge management (KM) and its impact on employee performance in various organizational contexts. This article aims to investigate how efficient management of knowledge resources affects individual performance in various contexts. The research method used in this article is a Systematic Literature Review (SLR). SLR is a methodological approach that involves a comprehensive and systematic analysis of existing literature in a specific research domain or topic. The research findings indicate a clear relationship between KM practices and employee performance, with a positive correlation in most cases. Keywords: Knowledge Management; Knowledge Sharing;  KM Practices; Employee Performance;  Job Performance